Cation-π induced association and nano-structured aggregate formation of water-soluble [PtII(diimine)(Ln-S,O)]+ complexes examined with high-resolution 1H and DOSY NMR : towards understanding their potential antimalarial activity - Kotze, Izak Aldert (Stellenbosch : Stellenbosch University, 2013)
Thesis (PhD)--Stellenbosch University, 2013.